2014
DOI: 10.1111/tan.12359
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G 3′ untranslated region polymorphisms influence the susceptibility for human papillomavirus infection

Abstract: Human leukocyte antigen (HLA)-G molecule acts as a potential factor for the regulation of immune responses and its expression in virus-infected cells may enable them to escape immunosurveillance. Besides its polymorphic promoter region, the 3' untranslated region (UTR) seems to play an important role in regulating HLA-G expression. In this study, we investigated the influence of HLA-G 14 bp (rs66554220) and +3142 (rs1063320) polymorphisms in 179 women with active human papillomavirus (HPV) infection and 143 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
0
28
1
Order By: Relevance
“…There is also evidence to support also a role of HLA-G molecules in susceptibility and outcome of human papilloma virus (HPV) infections. The alleles HLA-G 14bp INS , + 1537C (rs12722477), G * 01:01, G * 01:04 , and G * 01:06 have been associated with both high-grade squamous intraepithelial lesions and cervical cancer, while HLA-G 14bp DEL and + 3142C alleles have been identified as protective ( 130 135 ). These results are in agreement with the low levels of HLA-G5 expression in cervical cancer ( 136 ).…”
Section: Hla-g Impact In Viral Infectionsmentioning
confidence: 99%
“…There is also evidence to support also a role of HLA-G molecules in susceptibility and outcome of human papilloma virus (HPV) infections. The alleles HLA-G 14bp INS , + 1537C (rs12722477), G * 01:01, G * 01:04 , and G * 01:06 have been associated with both high-grade squamous intraepithelial lesions and cervical cancer, while HLA-G 14bp DEL and + 3142C alleles have been identified as protective ( 130 135 ). These results are in agreement with the low levels of HLA-G5 expression in cervical cancer ( 136 ).…”
Section: Hla-g Impact In Viral Infectionsmentioning
confidence: 99%
“…The specific characteristics of the qualified reports are presented in Table 1 . The included focused on the following virus types: hepatitis B virus (HBV), [ 11 , 15 , 16 ] HTLV-1, [ 9 , 10 ] human papillomavirus (HPV), [ 17 , 18 ] HCMV, [ 12 ] hepatitis C virus (HCV), [ 13 ] and human immunodeficiency virus (HIV). [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the non-allelic interaction and host genes may be associated with persistence of virus infection. Xu et al [ 18 ] showed that the relationship between 14-bp Ins/+3142G haplotype and HPV18 infection risk was prominent in a previous study. In addition, higher frequency of the 14-bp Ins /+3142G haplotype was observed in African-derived HIV positive patients when compared with that in controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations